Substance Use and Co-occurring Physical Health Problems: File Review of a Residential Drug and Alcohol Treatment Service. Issue 2 (2nd April 2020) - Osborne, Briony; Kelly, Peter J.; Larance, Briony; Robinson, Laura D.; Ivers, Rowena; Deane, Frank P.; Webber, Adrian; Kelly, David
Abstract: Objectives: Physical health conditions cause significant disability and mortality among people living with alcohol and other drug problems. There has been limited research on the prevalence of health problems among clinical samples of people with substance use disorders, particularly among those in residential treatment. Yet residential settings provide unique opportunity for responding to health needs. To better understand the health of people attending treatment for substance use disorders, this study conducted a file review to examine the prevalence of physical health problems as identified during routine residential care. Methods: A retrospective review of client files collected between 2013 and 2017 ( N = 172) was completed at a residential treatment service in NSW, Australia. Data were extracted to examine the prevalence of physical health problems recorded at entry into treatment. Correlates of health problems were estimated using bivariate descriptive analyses and logistic regression. Results: The majority of clients in treatment for substance use had a comorbid physical health problem (80.7%). Musculoskeletal problems were the most frequently reported medical issue (38.6%). Odds for some physical health problems were related to client gender, age, and primary substance of concern. Male gender remained the strongest predictor of dental health problems when controlling for age and substance type (odds ratio [ OR ] = 3.60). Primary alcohol use remained the strongest predictor of nutritional deficiencies when controlling for client age ( OR = 4.43). Among clients with a physical health problem and who had a treatment episode of at least 14 days ( n = 110), just over half (55.5%) were referred to a health-related practitioner or service during their treatment episode. Conclusions: This study contributes to the literature by reporting on the incidence of physical health problems among people in residential treatment for substance use disorders. The high prevalence of physical health morbidity iterates the role of non-medical staff working within drug and alcohol services in the identification of client health needs. The findings support calls for systematic screening of physical health as part of routine care for substance use disorders improved integration of substance treatment and the broader primary health care system.